2017
DOI: 10.5455/ijlr.20170613044844
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selenium Yeast and Vitamin E Supplementation on Growth, Nutrient Utilization and Immunity in Male Kids (Capra hircus)

Abstract: An experiment aimed to observe the effects of supplementation of selenium yeast and/or vitamin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Sethy et al [77] observed that redness and tenderness of meat increase but shear force value decrease as a result of addition of 0.3 mg Seas selenium yeast and 100 IU vitamin E in goat diet. Similarly it was proposed by Morrissey et al [78] that supplementation of diet with selenium yeast results in the rise of α-tocopherol in muscles but decrease the chances of lipid oxidation in muscles.…”
Section: Effect Of Yeast Addition On Meat Qualitymentioning
confidence: 71%
“…Sethy et al [77] observed that redness and tenderness of meat increase but shear force value decrease as a result of addition of 0.3 mg Seas selenium yeast and 100 IU vitamin E in goat diet. Similarly it was proposed by Morrissey et al [78] that supplementation of diet with selenium yeast results in the rise of α-tocopherol in muscles but decrease the chances of lipid oxidation in muscles.…”
Section: Effect Of Yeast Addition On Meat Qualitymentioning
confidence: 71%
“…Moreover, increase oxidative stability and vitamin E content in frozen meat of broilers supplemented with vitamin E (Konieczka et al, 2015). Additionally, Feeding kids goats 100 IU of vitamin E reduced malondialdehyde (MDA) concentration in meat (Sethy et al, 2014). The information about the influence of f eed on lipid oxidation of chevon is very few (Lee et al, 2008).…”
Section: Introductionmentioning
confidence: 99%